Comparative study on the antibacterial activities of four commercially available antiseptics- Dettol, Hexisol, Oralon and Betadine against staphylococcus aureus, klebsiella pneumoniae , bacillus cereus, and pseudomonas aeruginosa - Azam, Sakia Binte (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2017.